Multidimensional Fractionation of Particles - Frank, Uwe; Dienstbier, Jana; Tischer, Florentin; Wawra, Simon; Gromotka, Lukas; Walter, Johannes; Liers-Bergmann, Frauke; Peukert, Wolfgang (Separations, 2023)
The increasing complexity in particle science and technology requires the ability to deal with multidimensional property distributions. We present the theoretical background for multidimensional fractionations by transferring the concepts known from one dimensional to higher dimensional separations. Particles in fluids are separated by acting forces or velocities, which are commonly induces by external fields, e.g., gravitational, centrifugal or electro-magnetic fields. In addition, short-range force fields induced by particle interactions can be employed for fractionation. In this special case, nanoparticle chromatography is a recent example. The framework for handling and characterizing multidimensional separation processes acting on multidimensional particle size distributions is presented. Illustrative examples for technical realizations are given for shape-selective separation in a hydrocyclone and for density-selective separation in a disc separator.
Keywords: multidimensional separation; two-dimensional property distribution; size; shape; composition